REPRESENTASI ISU QUEER PADA MATERI KOMEDI POPON KEROK DALAM STAND-UP COMEDY TAYANGAN SOMASI CLOSE THE DOOR - Sudanta Wigas Hernawa; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2026)
This study aims to describe and analyze the various sign systems containing queer issues within Popon Kerok’s stand-up comedy material, specifically examining the discourse on queer issues constructed during his performance on the Somasi Close The Door program, while also exploring how Popon Kerok assigns meaning to queer issues within his comedy. Utilizing a qualitative approach, this study employs Roland Barthes’ semiotic analysis method to evaluate Popon Kerok’s comedy material on Somasi Close The Door. The results of this study reveal that the signs presented by Popon Kerok, both visually and verbatim in his comedy material, contain severe violations against the queer community. By utilizing a "close minded" persona, Popon's comedy material is accepted by audiences who share a heteronormative background.